2022
DOI: 10.3390/ijerph19105971
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Computer Aided Diagnosis in Chronic Low Back Pain: A Systematic Review

Abstract: Low Back Pain (LBP) is currently the first cause of disability in the world, with a significant socioeconomic burden. Diagnosis and treatment of LBP often involve a multidisciplinary, individualized approach consisting of several outcome measures and imaging data along with emerging technologies. The increased amount of data generated in this process has led to the development of methods related to artificial intelligence (AI), and to computer-aided diagnosis (CAD) in particular, which aim to assist and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 77 publications
(164 reference statements)
0
21
0
Order By: Relevance
“…AI and CS systems have already been shown to be a great support to physicians in the task of diagnosing and treating LBP and related pathologies in humans [ 8 , 9 ]. With this work, we aimed to provide a comprehensive review of the literature regarding the described applications of NLP-related methods to the care of patients affected by LBP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AI and CS systems have already been shown to be a great support to physicians in the task of diagnosing and treating LBP and related pathologies in humans [ 8 , 9 ]. With this work, we aimed to provide a comprehensive review of the literature regarding the described applications of NLP-related methods to the care of patients affected by LBP.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the most ground-breaking technologies have been explored in the care of LBP, including Artificial Intelligence (AI) and Computer Science (CS), which have seen their application in the care of LBP in several studies [ 8 , 9 ]. A promising trend in this field involves Natural Language Processing (NLP), a discipline at the intersection between CS, AI, and Linguistics.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence (AI) is developing rapidly with faster computing, advancement in hardware (e.g., fifth-generation mobile networks) and the advent of deep learning and artificial neural networks [ 1 ]. AI is found to be broadly benefitting modern medicine and clinical practice [ 2 ]. A range of AI-based applications, such as clinical and genomic diagnostics [ 3 , 4 ], chronic disease management [ 5 ], blockchain technology [ 6 ] and sophisticated surgical robots [ 7 ] have deeply reshaped medical practice in the 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…The advancements and an ever-increasing interest in machine learning (ML) and artificial intelligence (AI) approaches, with their applicability to different domains, were also reflected in different research efforts tackling LBP problems. In the recent period (2020-2022), several review studies have been presented focusing on the applications of ML and AI in the detection, classification, treatment, or management of LBP [8], [17], [18]. Although the respective review studies examined a large number of publications and research works within the LBP domain, it was observed that the number of papers tackling the LBP by exploiting ML and AI techniques, based on sEMG only, is still relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, only two papers were reported to deal with LBP by utilizing sEMG exclusively, whereas the additional three papers where combining sEMG with other types of information. In the most recent review study, by D'Antoni et al [18], the AI in the context of computer-aided diagnosis (CAD) in CLBP was reviewed. Similarly, only two studies were reported to deal with LBP by employing sEMG only [21], [22], and one study combined sEMG with kinematic variables [23].…”
Section: Introductionmentioning
confidence: 99%